Impact of subintimal plaque modification procedures on health status after unsuccessful chronic total occlusion angioplasty. Issue 6 (25th October 2017) - Hirai, Taishi; Grantham, J. Aaron; Sapontis, James; Cohen, David J.; Marso, Steven P.; Lombardi, William; Karmpaliotis, Dimitri; Moses, Jeffrey; Nicholson, William J.; Pershad, Ashish; Wyman, R. Michael; Spaedy, Anthony; et al.
Abstract: Objectives: We sought to determine the impact of subintimal plaque modification (SPM) on early health status following unsuccessful chronic total occlusion (CTO) PCI. Background: Intentionally dilating the subintimal space during unsuccessful CTO PCI to facilitate flow through dissection planes and improve success of repeat PCI attempts is a technique used by some hybrid operators, and may improve health status by restoring distal vessel flow despite unsuccessful CTO PCI. Methods: We studied 138 patients who underwent unsuccessful CTO PCI in a 12‐center CTO PCI registry. Safety was assessed by comparing in‐hospital outcomes of patients undergoing unsuccessful CTO PCI with and without SPM. The association between SPM and health status was quantified using the Seattle Angina Questionnaire Summary Score (SAQ SS), and the association between SPM and SAQ SS was determined using multivariable regression. Results: SPM was performed in 59 patients (42.8%). Complication rates were similar comparing those with and without SPM. At 1‐month, patients treated with SPM had larger increases in SAQ SS compared to patients who were not (28.3 ± 21.7 vs. 16.8 ±20.2, P  = 0.012), and SPM was associated with an adjusted mean 10.5 point (95% CI 1.4–19.7, P  = 0.02) greater SAQ SS improvement through 30 days. Conclusion: SPM was performed in almost half of unsuccessful CTO PCIs and was not associated with increased procedural complications. SPM was independently associated with better patient‐reported health status at 30 days. Further studies are needed to assess the necessity of subsequent PCI in patients with significant health status improvements after SPM.